Upaya Meningkatkan Kompetensi Guru Menggunakan Lingkungan Sebagai Sumber Belajar Melalui Latihan Terbimbing - Indrawanis, Indrawanis (JOEAI (Journal of Education and Instruction), 2021)
The purpose of this study was to improve the competence of teachers using the environment as a learning resource through guided exercises through the guidance of the principal at SDN 01 Labuah Gunaung, Lareh sago Halaban District, Limapuluh Kota Regency. This type of research is school action research, research using qualitative and quantitative approaches. The research procedure consists of the planning stage, the implementation stage, the observation stage, and the reflection stage. The research data was obtained from the teacher competency assessment using the environment as a learning resource. The results showed that the competence of teachers to use the environment as a learning resource through guided exercises with the average results of teacher competency assessment using the environment as a learning resource in Cycle I meeting I 60% and cycle I meeting II 75%. The teacher's activity during guidance got an average score in the first cycle of the first meeting 60% carried out and the first cycle of the second meeting 75% carried out. After reflection, there was an increase in cycle II, the average competence of teachers using the environment as a learning resource increased in the second cycle of the first meeting to 86% and the second cycle of the second meeting 95%. Teacher activity in guidance activities increased in the second cycle of the first meeting to 88% and the second cycle of the second meeting increased to 94%. In conclusion, through guided exercises, teachers can improve the competence of teachers using the environment as a learning resource at SDN 01 Labuah Gunaung, Lareh sago Halaban District, Limapuluh Kota Regency. Keywords: Teacher Competence, Guided Practice, Learning Resources